2013
DOI: 10.1590/s1516-05722013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do teor de óleo essencial de Baccharis trimera (Less.) DC. em diferentes embalagens durante o armazenamento

Abstract: Recebido para publicação em 18/09/2009 Aceito para publicação em 12/07/2012 RESUMO: O uso de plantas medicinais como fonte terapêutica é milenar e nos últimos anos o seu valor tem aumentado, tanto para a população quanto para a ciência. Várias empresas nacionais e internacionais empregam matéria-prima vegetal na elaboração de seus produtos, o que torna indispensável o cultivo comercial e o beneficiamento pós-colheita destas espécies. O objetivo deste trabalho foi avaliar o teor de óleo essencial de carqueja [B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(1 reference statement)
0
4
0
3
Order By: Relevance
“…In this study, the essential oil composition of Z. majdae was assessed at different temperatures and storage times. The harvesting and storage are important factors affecting the essential oil quality and chemical profile [39,40]. It has also been shown that the increase of temperature during storage decreases product quality [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the essential oil composition of Z. majdae was assessed at different temperatures and storage times. The harvesting and storage are important factors affecting the essential oil quality and chemical profile [39,40]. It has also been shown that the increase of temperature during storage decreases product quality [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…The harvesting and post-harvesting are extremely important for obtaining essential oil with higher quality, composition and for the product reaches the end of production chain (Ehlert et al, 2013;Silva et al, 2013). Thus, it is necessary to establish criteria to insure quality during processing and storage (Souza et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is necessary to establish criteria to insure quality during processing and storage (Souza et al, 2015). However, essential oil suffer numerous reactions, making the key storage quality and preservation of the physical and chemical composition (Guimarães et al, 2008;Silva et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…During storage, metabolic activity must be reduced, making medicinal plants less susceptible to deterioration. This can be achieved by reducing the water content of the product to safe levels, cooling or use of modified atmosphere in the system in which the medicinal plants are stored [7,11,12].…”
Section: Purpose Of the Storage Of Medicinal Plantsmentioning
confidence: 99%